The Determinants of Earnings Response Coefficients: Case Study from Chemical Industry in Indonesia - Sri Elviani; Zenni Riana; Ramadona Simbolon; Sri Puspa Dewi (Budapest International Research and Critics University, 2022)
This study aims to analyze the factors that influence the earnings response coefficient. This study uses secondary data that applies a multiple linear regression model with a sample period 2015-2018 of the basic chemical industry companies listed on the Indonesia Stock Exchange. The test results indicate that capital structure effect negatively to earnings response coefficient and profitability affect positively to earnings response coefficient. While growth opportunity, company size, audit quality and systematic risk partially do not affect the earnings response coefficient. This study provides an insight that growth opportunity, capital structure, company size, profitability, audit quality, systematic risk can affect the earnings response coefficient. This research is expected to assist investors in conducting fundamental analysis in the valuation model to determine the market reaction to the earnings information of a company, so that investors can find out the size of the share price response to the company's earnings information. The limitation in this study is the amount of samples that only take data on basic chemical industry companies listed on the Indonesian stock exchange.